Tingkat Kepuasan Pasien Terhadap Penumpatan Glass Ionomer Di Klinik Dokter Gigi Swasta - Dian Arita Dewi; Suharyono Suharyono; Siti Hidayati (Poltekkes Kemenkes Yogyakarta, 2017)
Background:Satisfaction is a state in which needs, wishes, and expectationscan bemet with a service received. Patients will feel satisfied if they think that the quality of service exceeds their needs, wishes and expectations. Tooth restoration is one of the method to repair tooth decay in order to return to its original shape and to function normally again for chewing. The material used often for the restoration is glass ionomer because it has advantages, namely the result of restoration has the same color as the teeth and it can release fluoride, which can help protecting teeth from secondary caries. Purpose: This research aims atobtaining an overview of patient’s satisfaction level with glass ionomer restoration at Private Dentist Clinic of X, Wates, KulonProgo. Methods: The research belongs to a descriptive research, with cross sectional survey research design.The population in this research was all patients who visited the Private Dentist Clinic of X, Wates, KulonProgo,whose age was limited to those above 17 years old. The sample size was 30 people. Results: The research results indicatedthat the patient’s satisfaction level with the tooth restoration using glass ionomer material at the Private Dentist Clinic ofX, Wates, KulonProgo, was 100% satisfied.The highest level of patient’s satisfaction in terms of sex was dominated by female of 56.7%. The highest level of patient’s satisfaction in terms of age was mostly 31-43 years old by 36.7%. The highest level of patient’s satisfaction in terms of education was high school graduates by 70%. Conclusions: It can be concluded from this research that all patients were satisfied with glass ionomer restoration at the Private Dentist Clinic of X, Wates, KulonProgo, with the highest level of satisfaction dominated by female, 31-43 years old, and high school graduates.